Development and Evaluation of a Reflective Solar Disinfection Pouch for Treatment of Drinking Water - Walker, D. Carey (American Society for Microbiology, 2004)
A second-generation solar disinfection (SODIS) system (pouch) was constructed from food-grade, commercially available packaging materials selected to fully transmit and amplify the antimicrobial properties of sunlight. Depending upon the season, water source, and challenge organism, culturable bacteria were reduced between 3.5 and 5.5 log cycles. The system was also capable of reducing the background presumptive coliform population in nonsterile river water below the level of detection. Similar experiments conducted with a model virus, the F-specific RNA bacteriophage MS2, indicated that the pouch was slightly less efficient, reducing viable plaques by 3.5 log units in comparison to a 5.0 log reduction of enterotoxigenic Escherichia coli O18:H11 within the same time period. These results suggest that water of poor microbiological quality can be improved by using a freely available resource (sunlight) and a specifically designed plastic pouch constructed of food-grade packaging materials.